(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Chronic non-healing ulcer is defined as a persistent defect in the skin for the period of more than six weeks and does not exhibit any tendency to heal following three or more months. Platelet-rich fibrin (PRF) and stromal vascular fraction (SVF) cells obtained from adipose tissue have been widely reported for diabetic wound heling. In this study, the efficacy of the SVF combined with PRF which contains abundant growth factors, for wound healing was evaluated using an animal model. PRF from venous blood was prepared from 8 donors and SVF from lipoaspirate were harvested from a single donor. Three groups were created (i) SVF + PRF as treatment group; (ii) Povidone Iodine (PI) - as standard of care; (iii) negative control group - allowing natural wound healing. Dorsal full thickness wounds were created in 40 male Sprague-Dawley (SD) diabetic rats. The SVF+PRF groups were subdivided into 3 groups having 40,000, one and two million cells per dose per application. On day seven of this study, rats were euthanized and wounds were analyzed microscopically and macroscopically. Wounds closed faster in the SVF + PRF group than in the control group or PI groups, with less inflammation, prominent signs of re-epithelization and blood vessels. The combination of SVF and PRF may provide an additive stimulatory effect to support angiogenesis and accelerate the wound healing process; accordingly. Our results suggest that the combination of SVF and PRF enhances wound healing.